Ontologies: a revamped cross-disciplinary buzzword or a truly promising interdisciplinary research topic? - Spyns, Peter; De Bo, Jan (Linguistica Antverpiensia, New Series – Themes in Translation Studies, 2021)
The following article provides an introductory overview of the different research domains (computational linguistics, termino graphy, artificial intelligence (AI), philosophy and database semantics) for which ontologies and the emerging field of the Semantic Web have become a main point of interest. It will be pointed out that each of these domains uses a different definition for an ontology. A specific ontology engineering methodology (VUB STAR Lab DOGMA) will be presented and emphasis will be put on the specific role and contribution of (multilingual) terminography in this ontology. In addition, we will explain what ontologies might offer to advance the state of the art of linguistics and terminography.